Integrasi Edukasi Parenting dan Kewirausahaan melalui Program Sekolah Orang Tua Hebat (SOTH): Strategi Pemberdayaan Ibu Rumah Tangga di Desa Karangwaluh, Kabupaten Ponorogo - Smita Catur Sudyantara; Mila Diana Sari; Susantriana Dewi; Rizqi Rahmawati; Rahmad Kurniawan; Takim Mulyanto (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Housewives play a crucial role in shaping children's character and supporting family economics. However, limited access to parenting education and entrepreneurial skills hinders their optimal contribution in both areas. This community service initiative aims to empower housewives in Karangwaluh Village, Sampung District, Ponorogo Regency through an integrated program combining parenting education and entrepreneurship training. The "Great Parent School" (Sekolah Orang Tua Hebat/SOTH) model was adapted as an intervention platform, enhanced with an entrepreneurship module. The program involved 25 housewives and was conducted in four sessions covering parenting principles, emotional intelligence, home-based business development, and financial literacy. Methods included lectures, group discussions, simulations, and business practice. Evaluation results indicated an increase in parenting knowledge (from 55% to 80%) and entrepreneurial understanding (from 45% to 75%). The program effectively enhanced mothers' skills in household management while building additional economic capacity. This model is recommended for replication in other rural areas.